Racial and ethnic differences in ADHD and LD in young school-age children: parental reports in the National Health Interview Survey. - Pastor, Patricia N. (Association of Schools of Public Health, 2005)
OBJECTIVES: Racial and ethnic disparities have been documented for many physical health outcomes in children. Less is known, however, about disparities in behavioral and learning disorders in children. This study uses data from a national health survey to examine racial and ethnic differences in identified attention deficit hyperactivity disorder (ADHD) and learning disability (LD). METHODS: The 1997-2001 National Health Interview Surveys obtained information from parents about the health and sociodemographic characteristics of children. Using these data, prevalence rates of identified ADHD and/or LD were estimated for Hispanic, African American, and white children 6-11 years of age. Racial and ethnic differences in health conditions, income, and insurance coverage were examined as possible explanations for disparities in parental reports of ADHD and LD, as well as the use of any prescription medication among children with ADHD. RESULTS: Hispanic and African American children, compared to white children, had parental reports of identified ADHD without LD less often, and adjustments for the confounding variables-birthweight, income, and insurance coverage-did not eliminate these differences. Hispanic and African American children, compared to white children, also had parental reports of ADHD with LD less often after adjustments for the effects of confounding variables. By contrast, after adjustments for confounding variables, Hispanic and African American children were as likely as white children to have LD without ADHD. Among children with ADHD, use of any prescription medication was reported less often for Hispanic and African American children than white children. These disparities in medication use persisted after adjustments for confounding variables. CONCLUSIONS: The prevalence of ADHD and the use of any prescription medication among children with ADHD differed among Hispanic, African American, and white children. These disparities could not be explained by racial and ethnic differences in other health conditions and sociodemographic variables.